Public Policy Reform and Police Prevention Practice: A Journey Upstream?. (22nd February 2021) - Bland, Nick; Calder, Amy; Fyfe, Nicholas R; Anderson, Simon; Mitchell, James; Reid, Susan
Abstract: This article contributes to a growing body of research on the police reforms in Scotland. It examines the particular place given to prevention in public policy and its impact on police practice. We show how public policy reconfigured the place and purpose of prevention for the police, with a focus on safety, wellbeing, and the prevention of harm. The research draws on qualitative data collected in four areas as part of a 4-year evaluation of the police reforms. We refine a public health typology of prevention and operationalize it empirically for the first time to analyse cases of innovative practice. We distinguish a pattern of prevention practice heavily weighted towards secondary prevention, focused predominantly on issues of crime and disorder. In fewer cases, the police applied primary and tertiary prevention, with a focus on vulnerability and harm. Looking in detail at two cases, we illustrate the importance of collaboration for the police, which created opportunities and brought additional resources and expertise to support new prevention approaches which had a significant impact on effectiveness. The police realized collaborative advantage through common aims, trust-building, and leadership. We do not suggest this demonstrates a transformation in police prevention; it illustrates successful police innovation, and identifies the potential to go further. The implications for policy and practice are to recognize the value to the police of investing in new partnerships. They create opportunities for the police to collaborate, innovate, and focus more sharply on the prevention of harm.